Postmortem diffusion MRI of the human brainstem and thalamus for deep brain stimulator electrode localization. Issue 8 (3rd June 2015) - Calabrese, Evan; Hickey, Patrick; Hulette, Christine; Zhang, Jingxian; Parente, Beth; Lad, Shivanand P.; Johnson, G. Allan
Abstract Deep brain stimulation (DBS) is an established surgical therapy for medically refractory tremor disorders including essential tremor (ET) and is currently under investigation for use in a variety of other neurologic and psychiatric disorders. There is growing evidence that the anti‐tremor effects of DBS for ET are directly related to modulation of the dentatorubrothalamic tract (DRT), a white matter pathway that connects the cerebellum, red nucleus, and ventral intermediate nucleus of the thalamus. Emerging white matter targets for DBS, like the DRT, will require improved three‐dimensional (3D) reference maps of deep brain anatomy and structural connectivity for accurate electrode targeting. High‐resolution diffusion MRI of postmortem brain specimens can provide detailed volumetric images of important deep brain nuclei and 3D reconstructions of white matter pathways with probabilistic tractography techniques. We present a high spatial and angular resolution diffusion MRI template of the postmortem human brainstem and thalamus with 3D reconstructions of the nuclei and white matter tracts involved in ET circuitry. We demonstrate registration of these data to in vivo, clinical images from patients receiving DBS therapy, and correlate electrode proximity to tractography of the DRT with improvement of ET symptoms. Hum Brain Mapp 36:3167–3178, 2015. © 2015 Wiley Periodicals, Inc.